2023
DOI: 10.1039/d3ra05018a
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic depolymerization of Kraft lignin to high yield alkylated-phenols over CoMo/SBA-15 catalyst in supercritical ethanol

Masud Rana,
Shubho Ghosh,
Theoneste Nshizirungu
et al.

Abstract: Kraft lignin was subjected to CoMo/SBA-15 catalyst in supercritical ethanol for high yield of alkylated-phenolic monomers production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…11–18 Considering that HDS and HER involve hydrogenation and dehydrogenation processes, which are inverse reactions, the activity and correlation of Co–Mo–S based catalysts between these two reactions are worthy of in-depth investigation. 19,20…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11–18 Considering that HDS and HER involve hydrogenation and dehydrogenation processes, which are inverse reactions, the activity and correlation of Co–Mo–S based catalysts between these two reactions are worthy of in-depth investigation. 19,20…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18] Considering that HDS and HER involve hydrogenation and dehydrogenation processes, which are inverse reactions, the activity and correlation of Co-Mo-S based catalysts between these two reactions are worthy of indepth investigation. 19,20 It has been found that the size, morphology and structure of MoS 2 have a certain correlation with its catalytic activity. 21,22 Studies have shown that the Co promotes MoS 2 based catalysts which have high performance for HER, are also active for HDS.…”
Section: Introductionmentioning
confidence: 99%